A Lattice-Tip Temperature-Controlled Radiofrequency Ablation Catheter: Durability of Pulmonary Vein Isolation and Linear Lesion Block - Reddy, Vivek Y; Neužil, Petr; Peichl, Petr; Rackauskas, Gediminas; Anter, Elad; Petru, Jan; Funasako, Moritoshi; Minami, Kentaro; Aidietis, Audrius; Marinskis, Germanas; Natale, Andrea; Nakagawa, Hiroshi; et al. (JACC. Clinical electrophysiology, 2020)
OBJECTIVES: This study was designed to evaluate lesion durability on invasive electrophysiologic remapping. BACKGROUND: The lattice-tip catheter generates a large thermal footprint during temperature-controlled irrigated radiofrequency ablation. In a first-in-human study, this catheter performed rapid point-by-point pulmonary vein isolation (PVI) and other linear atrial ablations. METHODS: In a prospective 3-center single-arm study, paroxysmal or persistent atrial fibrillation patients underwent PVI and, as needed, linear ablation at the cavotricuspid isthmus (CTI), mitral isthmus (MI), and/or left atrial roof; no other atrial substrate was ablated. Using the lattice catheter and a custom electroanatomic mapping system, temperature-controlled (Tmax 73° to 80°C; 2 to 7 s) point-by-point ablation was performed. Patients were followed for 12 months. RESULTS: A total of 65 patients (61.5% paroxysmal/38.5% persistent) underwent ablation: PVI in 65, MI in 22, left atrial roof in 24, and CTI in 48 patients. At a median of 108 days after the index procedure, protocol-mandated remapping was performed in 27 patients. The pulmonary veins (PVs) remained durably isolated in all but 1 reconnected PV-translating to durable isolation in 99.1% of PVs, or 96.3% of patients with all PVs isolated. Of 47 linear atrial lesions initially placed during the index procedure, durability was observed in 10 of 11 (90.9%) MI lines, all 11 (100%) roof lines, and all 25 (100%) CTI lines. After a median follow-up of 270 days, the 12-month Kaplan-Meier estimate for freedom from atrial arrhythmias was 94.4 ± 3.2%. CONCLUSIONS: Temperature-controlled lattice-tip point-by-point ablation showed not only highly durable PVI lesion sets, but also durable contiguity of linear atrial lesions.
Keywords: Catheter Ablation; Catheters; Temperature; lidé; prospektivní studie; Pulmonary Veins; Prospective Studies; katetrizační ablace; katétry; teplota; venae pulmonales; Humans